Comparison of the Effect of Different Alcohol Additives with Blended Fuel on Cyclic Variation in Diesel Engine - Obed M., Ali; Nik Rosli, Abdullah; R., Mamat; Abdul Adam, Abdullah (Elsevier Ltd, 2015)
Blended biodiesel-diesel fuel approved as a commercial fuel for unmodified diesel engine in many countries up to 20% (B20). Biodiesel fuel properties have limited their application in diesel engines at high blending ratio therefore, chemical additives introduced as a vaible option to improve these properties. Hence, in the present study, the effect of alcohol additived with biodiesel-diesel blended fuel B30 on diesel engine cyclic variations was investigated with 6% of two alcohol additives (ethanol and butanol). The in-cylinder pressure analyses results reveal that the lowest coefficient of variation indicated for the blended fuel B30 without additives. Furthermore, the engine cyclic variability increases above that of diesel fuel when using alcohol additives with blended fuel B30 with higher engine cyclic variation for the blended fuel B30 with ethanol compared to butanol. The results of wavelet power spectra analysis reveal that the in-cylinder pressure variations exhibit different types of behavior varying from intermittent fluctuations for B30 without additive to strongly periodic oscillations for B30 with alcohol additives compare to that of diesel fuel. Furthermore, the global wavelet spectra show that the overall spectral power increases when using alcohol additives with the blended fuel B30, which is in agreement with the coefficient of variation results.